COGNITIVE IMPAIRMENT IN HYPERTENSIVES - Tipnis, Natasha; Rajadhyaksha, Girish; Shah, Meghav (MNJ (Malang Neurology Journal), 2021)
Background: Hypertension and dementia increase parallel to age.Objective: The purpose of this study was to study the effect of hypertension on cognition before age-related cognitive impairment begins to set in.Methods: In this prospective, cross-sectional study conducted at a tertiary-care centre between May 2014 and December 2015, 300 (150 hypertensives and 150 normotensives) participants were compared. Patients were divided into groups according to age, gender, education, and duration of hypertension. The Hindi Mini-Mental State Examination (HMMSE) was used to detect cognitive impairment.Results: Overall, occurrence of cognitive impairment was 53 (35.3%) in hypertensives and 37 (24.7%) in normotensives. Below 60 years male and female hypertensives and normotensives had comparable mean HMMSE scores, although not statistically significant. Sixty years and above male and female normotensives achieved slightly higher HMMSE scores than male and female hypertensives, however this finding was statistically significant (p=0.002) for males â‰¥60 years. Among the cognitive domains, orientation to time (p=0.009), registration (p=0.018), recall (p=0.031), and 3 step command (p=0.014) were statistically different between hypertensives and normotensives. Periventricular white matter ischemia was discovered in 8 (5.3%) and 2 (1.3%) hypertensives and normotensives, respectively.Conclusion: Although hypertension was not statistically associated with cognitive decline in hypertensives <60 years, hypertensives >60 years showed statistical significance with cognitive decline. Furthermore, specific cognitive domains such as orientation to time, registration, recall, and 3 step command displayed statistical significance for cognitive decline. Future prospective, large-scale studies are warranted to investigate these and other possible associations.